DANI ARDOR’S TRAUMATIC EXPERIENCE, FEELINGS AND STRUGGLE TO GET HER SOCIAL LIFE IN THE MOVIE MIDSOMMAR BY ARI ASTER - Adinda, Herlita; Priyoto, Priyoto; Isminarni, Siti (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
The purpose of this research is to help people understand Mental Illness. The Writer chooses this Midsommar Movie as the main source for the analysis because the writer sees something complicated and intriguing to be analyzed and it can be used as knowledge and awareness through this movie. The movie is directed by Ari Aster. Additionally, the writer realizes that the issues and conditions that occurred in the movie also happen in real life. This study uses qualitative methods to analyze the data contained in the movie. This movie tells a story about Dani Ardor who just lost her family due to suicide. Dani, experiencing a painful tragedy about her family struggling to process her emotion and try to pretend as if she had overcome her grief by joining her boyfriend and his friends on a trip to Sweden and discovering a terrifying truth about the tradition that occurred in Harga every year. To analyze the problem formulation in this film, the writer uses Psychological approach and the theories that the writer chooses are Anxiety Disorder, Grief, PTSD, and Social Psychology. By applying the approach and theories, the writer concluded that Midsommar shows the struggle of Dani because she is unable to grief properly and affecting her mental health. The result of the research shows that people with Mental Illness need support from their relatives.